The impact of gender in cardiovascular medicine: Lessons from the gender/sex-issue in heart failure - Alberto M. Marra; Andrea Salzano; Michele Arcopinto; Lucrezia Piccioli; Valeria Raparelli (Monaldi Archives for Chest Disease, 2018)
Heart Failure (HF) is a major healthcare issue, given its high prevalence and incidence, the rate of comorbidities, the related high health-care costs and its poor outcome. In the last years mounting evidence revealed several differences between men and women affected by this clinical condition. Apart from the well-known difference in phenotype (HF with reduced ejection fraction (HFrEF) occurs more commonly in men, and HF with preserved ejection fraction (HFpEF) is more frequent in women) other relevant sex-related issues dwell upon epidemiology, presentation, risk stratification and management. These differences shed new lights on the possibility to consider HF as a prototype of the impact of gender/sex issue in cardiovascular medicine. A call for action and future strategies might help in the achievement of a cleaver patient-care.